Parasite intensities in relation to anthelminitic treatment in reindeer - Carlsson, Anja M.; Albon, Steve D.; Coulson, Stephen J.; Ropstad, Erik; Stien, Audun; Wilson, Ken; Loe, Leif Egil; Veiberg, Vebjørn; Irvine, R. Justin (Dryad Digital Repository, 2018)
one row per observation. Each row is a separate individual. Columns provide date of culling, treatment group, age and various measures of the abundance of the different stages of the two main parasites. See READ ME file for definitions of the variables